Increasing Academic Brand Awareness through Virtual Reality - Alexandru CAPATINA; George Cristian SCHIN; Dumitru RUSU (Revista de Management Comparat International)
In the global campus, Virtual Realities not only produce student-generated information and ideas, but they improve collaboration within and between the triple helix components: academic staff, students and employers. Using virtual reality (VR) technology, students will be able to be more prepared when they hit the real economy. Since technology is moving at a fast pace, it is time for universities to acknowledge VR technology use in view to increase their brand awareness and attract more prospective students. The aim of the paper is twofold. Firstly, it emphasizes the benefits of the VR application implemented within “Dunarea de Jos” University of Galati, the unique initiative in Romanian higher education system. Secondly, it attempts to identify the VR technology capabilities to increase the academic brand awareness in the internationalization strategies through a quantitative survey on professional networks, such ResearchGate and Academia.edu. We discuss the results to highlight the VR technology’s pivotal role in bridging the gaps between the methods to give lectures and worldwide students’ expectations to learn in a more entertaining way.